Causal association between antidiabetic drugs and erectile dysfunction: evidence from Mendelian randomization - Feng, Lin; Jinhua, Wu; Shulin, Guo; Jiangping, Xie; Zhongxiang, Liao; Xiaohong, Liao (Frontiers in Endocrinology, 2024)
Background Antidiabetic drugs are widely used in clinical practice as essential drugs for the treatment of diabetes. The effect of hypoglycemic drugs on erectile dysfunction has not been fully proven due to the presence of multiple confounding factors. Methods Two-sample Mendelian randomization (TSMR) was used to examine the causal effect of antidiabetic drugs (including metformin, insulin and gliclazide) on erectile dysfunction. We used five robust analytic methods, of which the inverse variance weighting (IVW) method was the primary method, and also assessed factors such as sensitivity, pleiotropy, and heterogeneity. Effect statistics for exposures and outcomes were downloaded from publicly available data sets, including open Genome-Wide Association Studies (GWAS) and the UK Biobank (UKB). Results In some of the hypoglycemic drug use, there was a significant causal relationship between metformin use and erectile dysfunction [Beta: 4.9386; OR:1.396E+02 (95% CI:9.13-2135); p-value: 0.0004), suggesting that metformin increased the risk of erectile dysfunction development. Also, we saw that gliclazide use also increased the risk of erectile dysfunction [Beta: 11.7187; OR:0.0125 (95% CI:12.44-1.21E+09); P value: 0.0125). There was no significant causal relationship between insulin use and erectile dysfunction [Beta: 3.0730; OR:21.6071 (95% CI:0.24-1942.38); p-value: 0.1806).Leave-one-out, MR-Egger, and MR-PRESSO analyses produced consistent results. Conclusion The use of metformin and gliclazide have the potential to increase the risk of erectile dysfunction. There is no causal relationship between the use of insulin and erectile dysfunction.